Adaptation To New Habits With UNLA (Usaha Nyata Lindungi Anda) - Ruhanda; Erwin Yulianto; Awan Setiawan (Jurnal Pengabdian Kepada Masyarakat, 2026)
Adaptation to New Habits during the Pandemic The Corona Virus Pandemic (Covid-19) is a major challenge in the world of education today, where the education sector is the main milestone for a country in creating a great nation. Precautions to prevent Corona Virus (Covid 19) in the world of education for all stakeholders always implement Clean and Healthy Living Behavior. The University environment is required to be able to prevent the spread of the virus and always implement Clean and Healthy Living Behavior. Therefore, Langlangbuana University implements several health protocol measures in the university environment, including the process of spraying disinfectants, the process of implementing Health protocols including Standard Operating Procedures and also coordination in responding to the Adaptation to New Habits. The implementation of these protocol measures is expected to suppress the spread of the Covid-19 virus in the campus area.